A study on the perceptions of unhealthy lifestyle and fast food consumption / Fauziah Osni... [et al.] - Osni, Fauziah; Hasaruddin, Nurlaila; Saidin, Rasyidah; Ayob, Shuhada; Abdullah, Shuhaila (2010)
The study of this research is to examine the relationship between fast food consumption and unhealthy lifestyle. A sample of 375 customers of Kentucky Fried Chicken (KFC) at Central Square, Sungai Petani Kedah was interviewed on two major issues. The fast food consumption and unhealthy lifestyle were examined by giving the questionnaire to the respondent in helping the researchers to collect the data. The data was analyzed with Pearson Correlation using Statistical Package for Social Science (SPSS) version 16.0. The results indicate that there are relationship between fast food consumption and unhealthy lifestyle where it can influence customer perception.